Tata Ruang Wilayah: Meaningful Participation Dalam Pembentukan Peraturan - Andriyansyah, Fahrudin; Azmani, Muhammad Usman Syahirul (Universitas Widya Gama Malang, 2024)
Community involvement and participation are very important in the drafting of regional regulations. If involvement and participation are neglected, the consequences will have an impact on the formal legitimacy of the regional regulations. The legalized of Malang City Regional Regulation Number 6 of 2022 on the Spatial Planning for the City of Malang for 2022-2042 in its development raises a big question, has the community been involved? Even if the community is involved, to what extent has this involvement been carried out? Does it meet reasonable eligibility criteria? The purpose of this study is to find out and analyse the application of meaningful participation in the establishment of Malang City Regional Regulation Number 6 of 2022 on Spatial Planning for Malang City for the 2022-2042 period. The research method used by the author is empirical legal research by conducting direct interviews with the Chairperson Regional Representative Council of the Malang City and Deputy Mayor of Malang in the Field of Economics and Development. The stages of preparing the Malang City Regional Regulation Number 6 of 2022 on Spatial Planning for the City of Malang for 2022-2042 include the stages of planning, preparation, discussion, evaluation, determination and publication. The implementation of meaningful participation in the formation of the Malang City Regional Regulation Number 6 of 2022 on the Malang City Spatial Plan for 2022-2042 was not carried out properly because the documents for forming the a quo Regional Regulation were prepared by the Malang City DPRD and the City Government.